2007
DOI: 10.1089/dis.2007.641
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disease Management Programs on Improving Diabetes Care for Individuals in Health-Disparate Areas

Abstract: In addition to race and ethnicity, specific geographic regions are associated with poorer outcomes of care. Individuals with diabetes experiencing health disparities typically have worse long-term outcomes, such as increased diabetes complications and mortality. Zip code mapping, or geocoding, was utilized in this study to identify regions of the United States with high diabetes prevalence rates and to identify areas with high densities of minority populations. Use of this methodology to examine the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The Zip Code Analysis Project revealed that 80% of minorities reside in 20% of U.S. Zip codes. 10 Sponsors can use this information to carefully select trial sites based on geographic distribution of ethnic/racial minority patients and physicians, keeping in mind the prevalence of the disease in that region.…”
Section: Reexamine Trial Design and Ethicsmentioning
confidence: 99%
“…The Zip Code Analysis Project revealed that 80% of minorities reside in 20% of U.S. Zip codes. 10 Sponsors can use this information to carefully select trial sites based on geographic distribution of ethnic/racial minority patients and physicians, keeping in mind the prevalence of the disease in that region.…”
Section: Reexamine Trial Design and Ethicsmentioning
confidence: 99%
“…(7, 8) Evidence shows that patients residing in low-income households receive lower quality diabetes care, even in settings where universal coverage for primary health care exists. (9, 10) Several studies have used mapping methods to assess diabetes-related processes and outcomes, including neurologic and renal complications (11), diabetes prevalence and treatment resources (12), and effectiveness of targeted programs to improve quality of diabetes care in zip codes with high minority populations (13). Other existing studies have analyzed disparities in diabetic amputations, but have generally focused on specific patient sub-groups or settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect on costs is still uncertain. [7][8][9][10][11][12][13] Health care systems around the world have nevertheless embraced disease management to address the gap between the care that should be provided to chronically ill patients and the care that physicians currently provide. 14 The US Centers for Medicare and Medicaid Services (CMS), for example, has implemented seven demonstration projects that focus on disease management, 15 including thirty-five programs in more than twenty states.…”
mentioning
confidence: 99%